Electromyography signal analysis of the fencing lunge by Magda Mroczkiewicz, the leading world female competitor in foil - Suchanowski, A.; Borysiuk, Z.; Pakosz, P. (Baltic Journal of Health and Physical Activity, 2011)
Background: Fencing lunge is the most important element of the fencing footwork technique. The aim of this study was to determine the dynamic model of the fencing lunge made by an experienced athlete, based on the EMG record of muscles activity: extensor carpi radialis of the right arm and rectus femoris of lower extremities.